A formação de professores na nova ordem de discurso da educação brasileira - Costa, Alexandre (Cadernos de Linguagem e Sociedade, 2010)
In this paper, we are concerned with the new educational order of discourse in Brazil and their consequences to teacher education. The technocratic reorganization of this macro institutional social field by the new liberal government in the past decade has caused a strategic control of political and pedagogical school resources with their submission to specific financial chains. It is mainly a question of reordering the previous intertextual references of school practices, but it is also a matter of rebuilding teachers’ identities by new genres and discourses.